1977
DOI: 10.1210/jcem-44-1-39
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Diurnal Pattern of Plasma Corticosteroids and Gonadotropins in Two Cases of Feminizing Adrenal Carcinoma: Measurements of Estrogen and Corticosteroid Production

Abstract: Two adult men with feminizing adrenal cortical carcinoma had measurements of their 24-h plasma corticosteroid and gonadotropin patterns as well as 24-h mean hormone levels of estradiol, estetrol, 11-desoxycortisol, DHEA-S, DHEA and testosterone. Cortisol, 11-desoxycortisol and estrogen production rates were also measured. The 24-h corticosteroid patterns showed preservation of the normal 24-h episodic and circadian patterns, albeit at higher levels. The cortisol production rates were markedly elevated despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As the patient had highly elevated E2 levels, we examined aromatase activity, aromatase protein, and tumor-specific aromatase gene promoter usage. To our knowledge, the patient was the youngest reported with an estrogen producing adrenal tumor [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and constituted the second report describing the preferential usage of alternative exons 1 of aromatase gene in adrenal tumors (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…As the patient had highly elevated E2 levels, we examined aromatase activity, aromatase protein, and tumor-specific aromatase gene promoter usage. To our knowledge, the patient was the youngest reported with an estrogen producing adrenal tumor [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and constituted the second report describing the preferential usage of alternative exons 1 of aromatase gene in adrenal tumors (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In literature only single cases have been reported in adults[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 19 21 22 23 24 25 25 ] and in pediatric population. [ 19 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 ] The largest published series does not exceed two[ 7 25 ] and three cases. [ 10 ] In our department we recorded five cases but only four have been published.…”
Section: Introductionmentioning
confidence: 99%
“…In oestrogen producing adrenal tumours, an elevation of urinary hCG levels was previously reported by several groups as well as non-suppressed serum pituitary gonadotrophin levels Rose et al, 1968;Boyer et al, 1977). In addition, increased serum levels and the post-operative normalization of pituitary gonadotrophins were reported in some patients with oestrogen producing adrenal tumours Rose et al, 1969).…”
mentioning
confidence: 74%
“…In addition, increased serum levels and the post-operative normalization of pituitary gonadotrophins were reported in some patients with oestrogen producing adrenal tumours Rose et al, 1969). Boyer et al (1977) suggested the possibility of hCG production and secretion from oestrogen producing adrenocortical neoplasms. In our case, serum hCG, LH and FSH levels were not elevated and immunoreactive hCG and LH were not detectable in the tumour tissue.…”
mentioning
confidence: 99%